Oil Politics and Subaltern Crises in Niger-Delta Poetry: A Study of Sophia Obi’s Tears in a Basket - EJIODU, Michael Onyeisi; NWOGA, Wisdom C. (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
The paradox of wealth and despair in the Niger-Delta region of Nigeria has inspired a growing body of works that interrogate the crises in the region. Poetry is a veritable medium for documenting these struggles and vocalising the aspirations of the people. Sophia Obi’s Tears in a Basket stands as a reflection of the socio-economic inequalities and environmental degradation faced by Niger-Delta communities as a result of oil exploration and exploitation. The collection critiques the exploitation of natural resources and marginalised groups, and exposes the complicity of state actors and multinational corporations involved in these injustices to the subalterns. This study adopts resistance framework to analyse Obi’s portrayal of class struggle and the commodification of resources in the region. It situates Tears in a Basket within the spectrum of Niger-Delta resistance literature and examines how the poet highlights the alienation and dispossession of local communities. The study reveals that Obi’s work successfully critiques the manipulation of the natural together with human resources, and highlights the collaboration of capitalist agencies and state operatives in mounting and prolonging inequality. Her clear imagery accentuates the cultural and environmental degradation fashioned and executed by oil exploration and extraction, while also reflecting the resilience and aspirations of the subaltern Niger-Delta people. The poems, in addition to the documentation of the lived realities, also envision a future where environmental justice and sustainability shall prevail. This is the conclusion of the paper. Finally, the paper underscores poetry as a vehicle for critiquing systemic exploitation and advocating reform.